Immigrants in Polish and German Online Media: A Comparative Analysis - Szylko - Kwas, Joanna; Gajlewicz - Korab, Katarzyna; Grutza, Anna; Jupowicz - Ginalska, Anna (Žurnalistikos tyrimai, 2018)
[full article and abstract in English]In this article, the authors present the results of their research conducted in Polish and German online media in 2016. The major topic of the abovementioned research was the European refugee crisis in Poland and Germany and its representation in websites of four quality newspapers: Wyborcza.pl, Rp.pl, Faz.net and Sz.de. The aim of this article is to analize the role of media in public opinion-shaping in both countries. Through a quantitative and qualitative evaluation of the data, the authors answered the following questions: 1) Are the media narratives of both countries different from each other? b) If so, how is the migration problem presented in Poland and in Germany? c) What are their most noticeable features?Among the most important conclusions are the following: 1) The media coverage of both countries is highly politicized; 2) Neither German nor Polish journalists of the opinion-forming quality newspapers did measurably support an isolationist policy.The research has been conducted within the scope of an International project called LEMEL (L’Europe dans les médias en ligne). This program was initiated by Cergy-Pontoise University and is now held annually. Several European countries participate in it (scientists from France, Germany, Italy, Poland and Romania are permanent members of the project’s research group). The aim of the project is a synchronous and diachronic comparative analysis of the content presented in their respective national online media.The analysis focuses on the way Europe and its problems are presented in the abovementioned media content.